PERLINDUNGAN HUKUM BAGI KONSUMEN SAAT MELAKUKAN TRANSAKSI JUAL BELI ONLINE - Dika Agmar Fachurrahman; Krisna Ade Saputra; Rudy Defri Susilo (Gapenas Publisher, 2023)
e-commerce has ushered in a new chapter in the global economy or digital economy. A high-tech based business, e-commerce brings a new look to traditional business. Online shopping has changed the communication model of producers and consumers in the world. Indonesia already has a legal basis for consumer protection, namely Law Number 8 of 1999 concerning Consumer Protection, and other laws and regulations that regulate the same matter. In this case, consumers must be given various protections. especially those who are very vulnerable to various possibilities that can harm the consumers themselves by traders who carry out buying and selling transactions online. There is no good intention. Online transactions between business people and consumers must have good intentions from the start. If consumers and business actors experience problems in buying and selling transactions, they can use the UUPK facility as a guideline for consumers, especially to fight for their rights to protect their interests. It is possible for commercial actors to find buyers. those who do not have good faith go through a similar process to solve problems. In essence, regulations related to consumer protection are not enough to just be a forum or legal vehicle for consumers and business actors. Several improvements and additions to regulatory substance still need to be added to protect all parties. Given the rapid pace of science, we must also be aware of the possibility of working against us.